PENINGKATAN KEAKTIFAN BELAJAR SISWA MELALUI PENGGUNAAN MEDIA DIORAMA PADA MATA PELAJARAN IPAS MATERI KEBERAGAMAN TRADISI DI KELAS III SEKOLAH DASAR - Anggraeni, Nadhifa; Indawati, Ninik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve students’ learning activeness through the use of diorama media in the IPAS subject, “Cerita Kampung Halamanku” chapter, for third grade elementary school students. This study used Classroom Action Research (CAR) based on the Kemmis and McTaggart model conducted in two cycles with 28 students as the subjects. Data collection techniques included observation, interviews, and documentation. The results showed that the use of diorama media was able to improve students’ learning activeness. In the pre-cycle, students’ activeness was 18,6% and categorized as very low. In cycle I, it increased to 60% and was categorized as fairly active, while in cycle II it increased to 92,2% and was categorized as very active. The improvement was seen in students’ ability to ask questions, answer questions, express opinions, and participate in learning activities. Therefore, diorama media is effective in improving students’ learning activeness in IPAS learning at elementary school.